Criteria for Selecting Patients for Inclusion in the Waiting List for Heart Transplantation - O. O. Tanska (Transplantation and artificial organs, 2020)
Objective. The aim of the study was to optimize the methods of selecting patients for inclusion in the «waiting list» for heart transplantation on the basis of available international data and the introduction of selection criteria.Materials and methods. The results of the study are based on survey data and dynamic monitoring of 49 patients (median age 38 (16; 65) years; 44 men, 5 women) who were treated from 2008-2018 in the centers: Republican Scientific and Practical Center «Cardiology», Minsk, Republic of Belarus; in the Center of cardiac surgery on the basis of Hospital «Feofania». Patients were examined during the initial examination, after 3 months, 6 months and after 1 year.Results and discussion. The first group consisted of 24 patients with CHF who were on the waiting list for orthotopic heart transplantation, for circulatory support, median age 40.95 (18.0; 65.0) years, men - 23, women - 1; The second group consisted of 25 patients with CHF who were on the waiting list fororthotopic heart transplantation without circulatory support, median age 38.56 (17.0; 64.0) years, men - 21, women - 4.Conclusions. Scientific novelty of the obtained results. For the first time in Ukraine, a road map has been developed and implemented and the dynamics of the movement of recipients who are in the «waiting list» for heart transplantation has been analyzed. Identified risk factors that affect the long-term outcomes and quality of life of patients with heart failure III-IV functional class according to the NYHA classification. Criteria for selection of patients for primary heart transplantation have been developed and implemented. For the first time in Ukraine, a «waiting list» for a heart transplant has been formed.